1998
DOI: 10.1055/s-0037-1615091
|View full text |Cite
|
Sign up to set email alerts
|

The Methylenetetrahydrofolate Reductase TT677 Genotype Is Associated with Venous Thrombosis Independently of the Coexistence of the FV Leiden and the Prothrombin

Abstract: SummaryA polymorphism, C→T677, in the methylenetetrahydrofolate reductase (MTHFR) gene has been identified as a cause of mild hyperhomocysteinemia, a risk factor for venous thrombosis. We have investigated the frequency of the TT genotype in 277 consecutive patients with confirmed deep venous thrombosis and 431 healthy subjects. The TT MTHFR genotype was more frequent in patients than in controls (25.6% vs. 18.1%; p = 0.016). The risk of thrombosis among carriers of this genotype was significantly increased [o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(79 citation statements)
references
References 29 publications
3
74
2
Order By: Relevance
“…Patients carrying FV Leiden individually (OR, 10.418), and in combination with PRT G20210A (OR, 85.198), or homozygous MTHFR C677T (OR, 81.133), had a very high estimated odds, while the calculated odds in carriers of the PRT G20210A and homozygous MTHFR C677T (OR, 20.812), was notably lower. This was in agreement with previous reports documenting the synergistic interaction between FV-Leiden and other prothrombotic SNPs [35], and enhanced risk of VTE in FV-Leiden when associated with PRT G2010A [36,37], or homozygous MTHFR C677T [20].…”
Section: Discussionsupporting
confidence: 93%
“…Patients carrying FV Leiden individually (OR, 10.418), and in combination with PRT G20210A (OR, 85.198), or homozygous MTHFR C677T (OR, 81.133), had a very high estimated odds, while the calculated odds in carriers of the PRT G20210A and homozygous MTHFR C677T (OR, 20.812), was notably lower. This was in agreement with previous reports documenting the synergistic interaction between FV-Leiden and other prothrombotic SNPs [35], and enhanced risk of VTE in FV-Leiden when associated with PRT G2010A [36,37], or homozygous MTHFR C677T [20].…”
Section: Discussionsupporting
confidence: 93%
“…The C677T and A1298A variants show reduced in vitro MTHFR enzyme activity (Frosst et al, 1995;van der Put et al, 1998). C677T/C677T homozygotes can display moderate hyperhomocysteinemia, which constitutes an independent risk factor for thrombophilia (Frosst et al, 1995;Arruda et al, 1997;Margaglione et al, 1998). A1298C/A1298C homozygotes, as well as carriers of either variant, do not suffer this risk, because their plasma homocysteine levels are within the normal range, but C677T/A1298C compound heterozygotes have increased homocysteine and reduced folate levels, similar to C677T/ C677T homozygotes (van der Put et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In three studies, C677T was shown to be a risk factor for venous thrombosis (132,136,137). The other studies failed to demonstrate an increased prevalence of C677T MTHFR among patients compared with controls.…”
Section: Case-control Studies Of Genetic Abnormalities Of Hcy Metabolismmentioning
confidence: 98%